LEARNING THE LANGUAGE OF INSTRUCTION IN UKRAINE: INTERNATIONAL STUDENTS' ATTITUDES - Oksana Zabolotna; Natalia Gut (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
Involvement of international students plays an important role in the process of every university development. This article presents the research conducted at Pavlo Tychyna Uman State Pedagogical University, one of the leading pedagogical universities in the central part of Ukraine. It considers language education of international students and their attitudes to learning the Ukrainian language as the language of instruction. The main tasks of this work were to study the organisation of educational process within the academic subject "Ukrainian language (as a second language)"; to examine international students' attitudes towards learning the Ukrainian language; to monitor students' satisfaction with the result of learning the Ukrainian language; to find out the difficulties that can affect the quality of language acquisition. 75 international students studying at non-linguistic faculties of the University who come from Turkmenistan, Azerbaijan, The Republic of Serbia, Uzbekistan were involved in the study. The purpose of the research was accomplished with the help of the questionnaire consisting of 9 closed-ended questions with an introductory section for indicating a participant's age, speciality and year of study etc. The preliminary results of the research show that students of different years of study initially have different ideas about the Ukrainian language as an academic discipline, but those with more developed language skills are more confident and motivated. Consequently, students are optimistic about their future development within the study and learning the Ukrainian language in higher education. The article also addresses the issues of mastering basic language skills in a relatively short period of time, the gap between the level of language proficiency and the volume of information students must learn in other disciplines, the language barrier. Finally, based on the results obtained and the reflection on their experience the authors suggested some recommendations to overcome possible difficulties in language acquisition.